Identifying species at extinction risk using global models of anthropogenic impact. (7th November 2014) - Peters, Howard; O'Leary, Bethan C.; Hawkins, Julie P.; Roberts, Callum M.
Abstract The International Union for Conservation of Nature Red List of Endangered Species employs a robust, standardized approach to assess extinction threat focussed on taxa approaching an end‐point in population decline. Used alone, we argue this enforces a reactive approach to conservation. Species not assessed as threatened but which occur predominantly in areas with high levels of anthropogenic impact may require proactive conservation management to prevent loss. We matched distribution and bathymetric range data from the global Red List assessment of 632 species of marine cone snails with human impacts and projected ocean thermal stress and aragonite saturation (a proxy for ocean acidification). Our results show 67 species categorized as 'Least Concern' have 70% or more of their occupancy in places subject to high and very high levels of human impact with 18 highly restricted species (range <100 km2) living exclusively in such places. Using a range‐rarity scoring method we identified where clusters of endemic species are subject to all three stressors: high human impact, declining aragonite saturation levels and elevated thermal stress. Our approach reinforces Red List threatened status, highlights candidate species for reassessment, contributes important evidential data to minimize data deficiency and identifies regions and species for proactive conservation.